PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN MEDIA BUKU POP UP TERHADAP MINAT BELAJAR IPS SEKOLAH DASAR (Studi Eksperimen Kuasi Siswa Kelas IIIA SD Negeri 63 Pekanbaru) - Ulfah, Aikah Mariah; Kurniaman, Otang; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of the low interest in social studies to students in class III SD Negeri 63 Pekanbaru. It can be known from the symptoms: 1) The students are less interested to study in the learning activities, and many students are still playing and noisier when learning. 2) Many students not pay attention when the teacher explains lessons. 3) Only a few students who actively ask and answer questions in class. 4) Students seem difficult to understand the material, and easy to forget the lesson that has been taught. The purpose of this study is to know the difference between the interest in studying the experimental class and control class and the effects of cooperative learning model and the pop-up books as a medium for the interests of studying IPS. Results of research on the experimental class applied cooperative learning model by using the pop-up book occurs an average increase student interest is significant, from 64.167 at the pretest to 88.792 at the posttest. While the control class, applied to conventional learning is also an increase in average interest in learning that is 63.429 at the pretest and 73.571 at the posttest. Based on the index gain, there is a difference in improving learning IPS students significant between experimental class and control class. The average increase (gain) on experimental class is 0.672 with the medium category, while the control class 0.079 with low category. Cooperative learning model and pop-up books media affect the interest of studies IPS students. The effect of the application amounted to 37.45%. Keywords: Cooperative, pop-up books, interest of studying IPS